Latihan Fisik untuk Mengurangi Tekanan Intraokular pada Glaukoma: Tinjauan Sistematik - Apriandary, Ni Putu Dian; Rahayu, Ni Kompyang (PT Kalbe Farma Tbk., 2025)
Introduction: Glaucoma is a common eye condition that poses a risk to vision, as it involves elevated intraocular pressure (IOP) and can lead to vision impairment. Elevated intraocular pressure (IOP) and inadequate ocular perfusion are the basic theories of glaucoma development and progression. Methods: Literature within the last 10 years was searched through PubMed and Googleusing the specified keywords: “Glaucoma” (title), “Intraocular Pressure (IOP)” (all fields), and “Physical Exercise” (all fields). The PRISMA method is used to process journal selection. Results: Dynamic exercises such as cycling and jogging have been shown to significantly reduce intraocular pressure (IOP), particularly in patients with glaucoma, whereas isometric activities like weightlifting or head-down yoga poses temporarily increase IOP. Breathing exercises such as yogic pranayama can lower IOP by stimulating parasympathetic activity and improving aqueous humor outflow without elevating ocular venous pressure. Conclusion: The decrease in IOP and increase in OPP after dynamic exercises such as cycling and jogging were related to the intensity of the exercise. No cure is available; management is to prevent further damage and vision loss. Physical exercise influences the IOP, ocular perfusion, neuroprotection, and mental health in patients with glaucoma. This article discusses the benefits of physical exercise in reducing IOP and its potential risks in glaucoma patients.